PENGARUH PENDIDIKAN KESEHATAN MELALUI METODE CERAMAH DENGAN METODE DISKUSI TERHADAP PENGETAHUAN DAN SIKAP TENTANG NARKOTIKA, PSIKOTROPIKA, ZAT ADIKTIF (NAPZA) PADA SISWA SMU SWASTA RK DELI MURNI DISKI KECAMATAN SUNGGAL KABUPATEN DELI SERDANG TAHUN 2016 - Merlina Sinabariba (STIKes Santa Elisabeth Medan, 2017)
From the observation, it was found some students of Private High School of RK Deli Murni comsumed Narcotics, Psychotropica, Addictive Substances (NAPZA). This was caused by lack of knowledge and attitudes about NAPZA, so it is necessary to do health education to increase student’s knowledge and attitude. Health education can be done by using lecture and discussion methods. The research objective was to understand the effects of health education through lecture and discussion method on knowledge and attitudes about NAPZA among students of Private High School RK Deli Murni Diski, Sunggal Subdistrict, Deli Serdang District. The type of research was quasi experimental design with Pretest-Posttest Group Design. The population included all the students in Private High Schools of RK Deli Murni. The samples were 60 students and divided into two groups: 30 students were in lecture group and 30 students were in discussion group. The analysis of the data used Independent t-test. The result of the research showed there was an effect of health education through lecture and discussion method toward knowledge (p = 0.031) and the attitude (p=0,011). The mean of knowledge in lecture group was 5,03 with deviation standard was 1,75 and the mean of knowledge in discussion group was 5,93 with deviation standard was 1,39. The mean of attitude in lecture group was 7,07 with the deviation standard was 3,06 and the of attitudein discussion group was 8,93 with deviation standard was 2,41. It is suggested to School Master of Private High School of RK Deli Murni to use discussion method in delivering message about NAPZA to the students because it was proved more excelent than lecture method to increase student’s knowledge and attitude. It is needed to make collaboration with health office to give health education especially about NAPZA.